Phenomenology and Ideology: Tuckett’s “Phenomenological” Founding of “Social Science Proper” - Srubar, Ilja (Human Studies, 2020)
CRIS-Team Scopus Importer:2020-07-24

Schutz's sociology of knowledge - Srubar, Ilja (The Anthem Companion to Alfred Schutz, 2022)
CRIS-Team Scopus Importer:2024-12-16

The Relevance of the Irrelevant - Srubar, Ilja (Relevance and Irrelevance, 2018)
The formation of cultural worlds happens through selective mechanisms inherent to social action and communication. In social theory such selectivity is often thematized as the problem of relevance, i.e. as the problem of preferences orienting action and transforming open possibilities into the reality of specific life forms. The article thematizes the selective "machineries" of pragmatic relevance working in habitus, language, institutions, discourses and narratives. It argues that approaching the formation of cultural life forms from this point of view confronts us with the fact that the selective processes do not annihilate the excluded possibilities, which instead remain on the horizon of the respective universe of meaning while still forming its order. The mutual relation of relevance and the irrelevant within the construction of social reality is discussed in the final part of the paper.
CRIS-Team WoS Importer:2019-06-18